3(2x-3)=6(x+1)-15

Simple and best practice solution for 3(2x-3)=6(x+1)-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-3)=6(x+1)-15 equation:


Simplifying
3(2x + -3) = 6(x + 1) + -15

Reorder the terms:
3(-3 + 2x) = 6(x + 1) + -15
(-3 * 3 + 2x * 3) = 6(x + 1) + -15
(-9 + 6x) = 6(x + 1) + -15

Reorder the terms:
-9 + 6x = 6(1 + x) + -15
-9 + 6x = (1 * 6 + x * 6) + -15
-9 + 6x = (6 + 6x) + -15

Reorder the terms:
-9 + 6x = 6 + -15 + 6x

Combine like terms: 6 + -15 = -9
-9 + 6x = -9 + 6x

Add '9' to each side of the equation.
-9 + 9 + 6x = -9 + 9 + 6x

Combine like terms: -9 + 9 = 0
0 + 6x = -9 + 9 + 6x
6x = -9 + 9 + 6x

Combine like terms: -9 + 9 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 21x-2=4(5x+3)-10 | | X+13=-14 | | .7x+.05(6-x)=.1(-88) | | |p-7|+13=5 | | s+2-3-16=0 | | 80=3x+19 | | 22+8x=-5+3(5x-5) | | -2(a-5)=27-2a | | 20(x-1)=-4(5-x)+16x | | y^2+11y-12=0 | | 12y^2-4y^4= | | 4x-2(x-7)=4 | | 6x^2+5x-8=-4 | | 43+63+57+4x=55 | | .18y+.04(y+6000)=1780 | | us+uz=t | | 7n=85n | | 2r-(-4+r)=7-2r | | 32y+5y=2 | | 6x-12+2x=7+8x-19 | | 7x+1x=3x+3 | | 5x(x)-13x+6=0 | | 2x+3(x+1)=13 | | 24x^2+76x+60=0 | | 3(2x-5y)=30 | | w-3=2w+5 | | -(3x+1)+2(1-2x)=-13 | | -5x-4=-2x+8 | | 2(3/8)= | | 61=6-8x-3 | | -10n+3(8+8n)=-6(m-4) | | (-19)-13= |

Equations solver categories